Penerapan Restorative Justice dalam Tindak Pidana KDRT Rizky Billar terhadap Lesti Kejora - Malfa Calistaningtyas; Misdaliah Misdaliah; Atika Novianty; Luku Isa Ramadani; Claudio Gratiano Laga Kota; Eggy Rizki Fajari (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Domestic Violence is a criminal offense that remains a serious issue in Indonesia due to its significant impact on victims, families, and the social environment. One of the cases that attracted public attention was the domestic violence case involving Rizky Billar and Lesti Kejora, which was resolved through a Restorative Justice approach. This study aims to analyze the implementation of Restorative Justice in resolving domestic violence cases and to examine its conformity with Indonesian criminal law provisions. The research employs a normative legal research method using statutory and case approaches supported by library research. The findings indicate that Restorative Justice emphasizes relationship restoration, offender accountability, and victim participation in the resolution process. This approach is not solely focused on punishment but also on restoring the losses suffered by victims and rebuilding social harmony. Furthermore, Restorative Justice provides an alternative mechanism for resolving certain criminal cases through peaceful settlement while considering the interests of all parties involved. However, its application in domestic violence cases must be carried out carefully and selectively to ensure victim protection and the achievement of justice, legal certainty, and legal benefit.